Water quality assessment and decolourisation of contaminated ex-mining lake water using Bioreactor Dye-eating Fungus (BioDeF) system: a real case study - Mohd Hanafiah, Zarimah; Azmi, Ammar Radzi; Wan-Mohtar, Wan Abd Al Qadr Imad; Olivito, Fabrizio; Golemme, Giovanni; Ilham, Zul; Jamaludin, Adi Ainurzaman; Razali, Nadzmin; Halim-Lim, Sarina Abdul; Wan Mohtar, Wan Hanna Melini (Multidisciplinary Digital Publishing Institute, 2024)
The environmental conditions of a lake are influenced by its type and various environmental forces such as water temperature, nutrients content, and longitude and latitude to which it is exposed. Due to population growth and development limits, former mining lakes are being converted to more lucrative land uses like those of recreational zones, agriculture, and livestock. The fungus Ganoderma lucidum has the potential to be utilised as a substitute or to perform synergistic bacteria-coupled functions in efficient contaminated lake water treatment. The purpose of this paper is to evaluate the water quality and water quality index (WQI) of an ex-mining lake named Main Lake in the Paya Indah Wetland, Selangor. Furthermore, the current work simulates the use of a Malaysian fungus in decolourising the contaminated ex-mining lake by the BioDeF system in a 300 mL jar inoculated with 10% (v/v) of pre-grown Ganoderma lucidum pellets for 48 h. According to the results, the lake water is low in pH (5.49 ± 0.1 on average), of a highly intense dark brownish colour (average reading of 874.67 ± 3.7 TCU), and high in iron (Fe) content (3.2422 ± 0.2533 mg/L). The water quality index of the lake was between 54.59 and 57.44, with an average value of 56.45; thus, the water was categorized as Class III, i.e., under-polluted water, according to the Malaysian Department of Environment Water Quality Index (DOE-WQI, DOE 2020). The batch bioreactor BioDeF system significantly reduced more than 90% of the water’s colour. The utilization of Ganoderma lucidum as an adsorbent material offers a variety of advantages, as it is easily available and cultivated, and it is not toxic.